How to identify which patients with asymptomatic carotid stenosis could benefit from endarterectomy or stenting - Paraskevas, Kosmas (Henry Stewart Talks, 2018)
Some facts about strokes, Microemboli detection on transcranial Doppler, Carotid plaque echolucency on duplex ultrasound, Progression of the severity of carotid artery stenosis, Silent embolic infarcts on brain CT or MRI, Reduced cerebrovascular reserve, Size of juxtaluminal hypoechoic area, Identification of intraplaque haemorrhage using MRI, Carotid ulceration